PERSEPSI MASYARAKAT TERHADAP MANFAAT JAMINAN KESEHATAN BAGI HAK PENGGUNA KARTU BPJS DI PUSKESMAS BERSERI KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN - Yulianingsih Yulianingsih; Hambali Hambali; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the public's perception of the benefits of health insurance for the rights of BPJS card users at the Berseri Health Center, Pangkalan Kerinci District, Pelalawan Regency. The type of research used is descriptive quantitative research, which is looking for an overview of research phenomena, namely the Berseri Health Center lacks manpower, does not have competent resources, does not have complete data, lacks transparency, and so on. The reason for using this type of descriptive research is because the variable under study is a single variable so it does not require hypothesis and statistical testing, it just gives an idea of how the perception or point of view of BPJS patients on the benefits of health insurance at the Berseri Health Center, Pangkalan Kerinci District, Pelalawan Regency. The sample used was BPJS participants at the Berseri Health Center, Pangkalan Kerinci District, Pelalawan Regency. The data collection technique used a questionnaire. Based on the results of research and discussion, it has been concluded that based on data recapitulation regarding public perceptions of the benefits of health insurance at the Berseri Health Center, Pangkalan Kerinci District, Pelalawan Regency in 2021 where from 4 indicators namely promotive, preventive, curative and rehabilitative and or as many as 22 statement items responded to by respondents on This study concludes that their perception of the benefits of BPJS health insurance at the Berseri Health Center is good with a percentage of 75.53% in the range of 51%-75%.Key Words: Public Perception, Health Insurance, BPJS.